PEMBERDAYAAN PEREMPUAN MELALUI PROGRAM SIMPAN PINJAM KELOMPOK PEREMPUAN (SPP) DI UPDB BUMDESMA TANJUNGKERTA KABUPATEN SUMEDANG - Anisa, Dini (JRPA - Journal of Regional Public Administration, 2025)
Women’s empowerment is driven by the need to improve the welfare and independence of housewives in the Tanjungkerta District, most of whom do not have a fixed income, have limited education, limited skills, and limited access to economic resources. The Women’s Group Savings and Loan Program (SPP) managed by UPDB BUMDESMA Permata Sejahtera Abadi LKD is a government strategy to empower women by providing access to group business capital. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results show that women’s empowerment through the SPP program, viewed from the indicators Envision, Educate, Eliminate, Express, Enthuse, Equip, Evaluate, and Expect has not been running well enough due to several obstacles, such as the tendency to use loan funds for consumption, lack of business management skills, limited access to training and mentoring, and weak understanding of the program’s objectives. To address these issues UPDB BUMDESMA has undertaken various efforts such as coaching, monitoring and evaluation, providing entrepreneurship training, and collaborating with other institutions such as MSMEs. Nevertheless, the program still needs to be improved through more sustainable and comprehensive empowerment strategies to maximize its impact.